High Molecular Weight Fucoidan Loading Into and Release from Hyaluronate‐Based Prefabricated Hydrogel and its Nanogel Particles Controlled by Variable Pitch and Differential Extensional Shear Technology of Advanced Twin Screw‐Based System. Issue 5 (4th December 2022) - Khatun, Mst Rita; Bhattacharyya, Amitava; Taheri, Shiva; Ham, Hyeong‐wook; Kim, Hongkyun; Chang, Seok Hong; Noh, Insup
Abstract: Efficient incorporation of high molecular weight drug into prefabricated hydrogel and its delivery are big challenges in its applications to drug delivery and tissue regeneration using a 3D bioprinting system. In this work, a new method of loading a model high molecular weight drug (fucoidan with 200 kDa) into prefabricated hyaluronate‐based terpolymeric gel is developed by using an advanced screw‐based extrusion printing system. This system effectively incorporates the fucoidan biomolecules into the prefabricated crosslinked gel within 60 s at significantly higher percentages without much change in gel properties. Less damage in gel network is achieved through variable pitch and differential extensional shear mechanism by optimization of bioprinting conditions. Importantly, fucoidan‐loaded nanoparticles (NPs) are developed using the advanced extrusion system at high screw rpm and with increased residence time using recirculation. The encapsulation efficiency, sustained release of fucoidan, and in vitro cell culture studies confirm the nontoxic nature of the drug‐loaded gels and nanogels at lower doses, exhibiting the biomedical application potentials of this advanced screw‐based extrusion printing system and drug‐loaded NPs formation in pharmaceuticals, 3D bioprinting, tissue engineering as well as maximal drug loading into and sustained release from prefabricated gels. Abstract : Loading of long chain fucoidan biomolecules into prefabricated hyaluronate‐based gel and synthesis of fucoidan‐loaded gel nanoparticles are achieved using an advanced twin screw extrusion system through differential extensional shear and recovery mechanism of mechanically driven gel network. This novel system is potential for efficient and maximal drug loading and for the drug‐loaded NPs formation with higher efficiency and sustained release.